2005
DOI: 10.1074/jbc.m504772200
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of a Complex Target Using DNA Aptamers

Abstract: In vitro selection of single-stranded nucleic acid aptamers from large random sequence libraries is now a straightforward process particularly when screening with a single target molecule. These libraries contain considerable shape diversity as evident by the successful isolation of aptamers that bind with high affinity and specificity to chemically diverse targets. We propose that aptamer libraries contain sufficient shape diversity to allow deconvolution of a complex mixture of targets. Using unfractionated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 49 publications
(37 reference statements)
1
19
0
2
Order By: Relevance
“…In the single-step method most enrichment occurred in the last 4 cycles, but no peak was reached suggesting that further enrichment could be achieved by additional cycles. The initial increase of motifs 4 and 5 followed by a plateau is typical of SELEX,[25] and shows that enrichment was complete after three or four rounds. Linker 6 is different; it was first detected at low (0.01%) abundance in Round 4 and then increased more rapidly than any other motif in Round 5.…”
Section: Resultsmentioning
confidence: 90%
“…In the single-step method most enrichment occurred in the last 4 cycles, but no peak was reached suggesting that further enrichment could be achieved by additional cycles. The initial increase of motifs 4 and 5 followed by a plateau is typical of SELEX,[25] and shows that enrichment was complete after three or four rounds. Linker 6 is different; it was first detected at low (0.01%) abundance in Round 4 and then increased more rapidly than any other motif in Round 5.…”
Section: Resultsmentioning
confidence: 90%
“…In particular, the concept of 'complex-target' selection, where targets are not pure proteins but may include whole organisms, intact cells or human plasma, may lead to the identification of aptamers against proteins that can only be targeted in their physiological milieu. [65][66][67][68] In some biological systems, agonists may be of more therapeutic importance than antagonists and we envision that agonistic aptamers will soon be realized. Furthermore, the increasing focus on the use of aptamers as tools for diagnostics, target validation and drug discovery will maximize the potential of aptamers in therapeutics.…”
Section: Prospectsmentioning
confidence: 99%
“…This leaves unanswered the ultimate question of why there are 2 aptamers for thrombin. We suspect that the solution to this mystery is related to the small library used by Bock, which may have had a diversity of less than 10 12 , and the tendency of aptamers to converge on a single epitope after many rounds of selection (Fitter and James 2005), such as the 11 rounds applied by Tasset. We are currently investigating these factors using next generation sequencing and hope to show how they contributed to the discovery of the thrombin aptamers in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Electrophoresis of thrombin solutions stored at room temperature showed that the intensity of the 27-kDa band increased with time. b-thrombin does not have an intact exosite 1 (Fitter and James 2005), and therefore APT-15 should have a lower affinity for it. Blots interrogated with fluorescent APT-15 and APT-29 (Fig.…”
Section: Resultsmentioning
confidence: 99%